Caracterização ultrassonográfica dos órgãos da cavidade celomática do jabuti-piranga (Chelonoidis carbonaria SPIX, 1824) - Meireles, Yara Silva (2014)
In this study we describe the sonographic morphology and sintopy of the coelomic cavity organs of red-footed tortoise. Thirty eight healthy animals, 19 males and 19 females, were anesthetized with ketamine and midazolam and contained in ventral decubitus position for scanning the coelomic cavity through the cervical and pre- femoral access with multifrequency sector transducer. Several body measurements and heart rate were measured and the morphology, echogenicity and sintopy of the heart, thyroid, liver, gallbladder, stomach, intestines, ovaries, oviduct, testis, kidney and bladder were evaluated. The heart showed two atria and one ventricle with trabecular thick wall. In cardiac basis was visualized the oval and echogenic thyroid, which showed a positive correlation with the weight of the animal. The liver, gallbladder and digestive system were similar to those seen in mammals and turtles. However, the tortoise liver was more hyperechoic relative to mammals. The kidneys were seen as triangular structures, hypoechoic, homogeneous and vascularized and the bladder was observed mostly as elongated with anechoic content and its wall was seen as a thin hyperechoic line when there was free fluid. The testes were observed as elongated, homogeneous and hyperechoic in relation to kidney structures. The ovarian follicles were seen as a hyperechoic echogenic balls of variable size and quantity, the oviduct as a sigmoid tubular structure and eggs as thin hyperechoic lines with posterior acoustic shadowing. In some animals, there was a variable amount of anechoic fluid around the heart and in the coelomic cavity.